IMPROVING THE MECHANISMS OF FORMING THE SPIRITUAL IMAGE OF LEADING EMPLOYEES OF THE EDUCATIONAL INSTITUTION THROUGH FORSITE TECHNOLOGY - Nuriyeva Umida Buribayevna; Baybayeva Muxayyo Xudaybergenovna (Web of Journals Publishing, 2025)
In this study, the importance of foresight technology in the formation of the moral image of the educational institution's leaders and the mechanisms of its improvement are studied. Foresight technology, that is, the methodology of foreseeing and forecasting the future, helps to determine the directions of development of executives and improve the processes of making strategic decisions. The research shows how foresight technology is used in the educational system, especially in the formation of the spiritual image of leaders, and how pedagogical leadership and psychological approaches play an important role in this process. Also, practical recommendations and strategies for improving the mechanisms of formation of the moral image of the leaders of the educational institution have been developed. The study emphasizes the need to introduce innovative approaches to the management processes of the educational system and shows how foresight technology should be adapted to the long-term development strategy.
Keywords: Foresight technology, educational institution, management staff, moral image, educational management, strategic decisions, pedagogical leadership, psychological approach, development strategy, innovative management.